Inventory Control and Management - Waters, C. D. J. (C. Donald J.), 1949- (John Wiley & Sons Ltd, 2003)
Holding stock is expensive – problems of inventory control almost universal. Over the past decade organisations have been trying to improve customer service while lowering stocks and increasing the speed of material flow through their supply chains. This completely updated new edition reviews current thinking on inventory management. It emphasises the growth of e-commerce, and the trend away from classical models based on economic order quantities and towards dependent demand systems. The author sets inventory management in its broader context, discussing the important trends and pressures for change. The main approaches are discussed and evaluated, giving the reader a broad appreciation of the principles involved. Some quantitative ideas are developed in the text, but the author has kept the mathematics to a minimum, focusing on practical examples and calculations on spreadsheets